Dynamics of pastoral traditional ecological knowledge: a global state-of-the-art review ... : ديناميات المعرفة البيئية التقليدية الرعوية: مراجعة عالمية حديثة ... - Abolfazl Sharifian; Álvaro Fernández‐Llamazares; Hussein T. Wario; Zsolt Molnár; Mar Cabeza (OpenAlex, 2022)
Traditional ecological knowledge enables pastoralists to cope with social-ecological changes, thereby increasing the sustainability of their practices and fostering social-ecological resilience.Yet, there is a significant knowledge gap concerning the extent to which pastoral traditional ecological knowledge has changed over time at the global level.We aim to fill this gap through a systematic literature review of 288 scientific studies on pastoral traditional ecological knowledge.We reviewed 152 papers in detail (selected randomly from the 288) for their content, and focused specifically on 61 papers that explicitly mentioned one of the four types of knowledge transition (i.e., retention, erosion, adaptation, or hybridization).Studies on pastoral traditional knowledge represent less than 3% of all the scholarly literature on traditional ecological knowledge.Geographical distribution of the 288 case studies was largely biased.Knowledge domains of pastoral knowledge such as herd and livestock management, ... : تمكن المعرفة البيئية التقليدية الرعاة من التعامل مع التغيرات الاجتماعية والبيئية، وبالتالي زيادة استدامة ممارساتهم وتعزيز المرونة الاجتماعية والبيئية. ومع ذلك، هناك فجوة معرفية كبيرة فيما يتعلق بمدى تغير المعرفة البيئية التقليدية الرعوية بمرور الوقت على المستوى العالمي. نهدف إلى سد هذه الفجوة من خلال مراجعة منهجية للأدبيات لـ 288 دراسة علمية حول المعرفة البيئية التقليدية الرعوية. قمنا بمراجعة 152 ورقة بالتفصيل (تم اختيارها عشوائيًا من 288) لمحتواها، وركزنا بشكل خاص على 61 ورقة ذكرت صراحة واحدة من الأنواع الأربعة لنقل المعرفة (أي الاحتفاظ أو التعرية أو التكيف أو التهجين). تمثل الدراسات حول المعرفة التقليدية الرعوية أقل من 3 ٪ من جميع الأدبيات العلمية حول المعرفة البيئية التقليدية. كان التوزيع الجغرافي لدراسات الحالة البالغ عددها 288 دراسة متحيزًا إلى حد كبير. تمت تغطية مجالات المعرفة الرعوية مثل إدارة القطعان والماشية والعلف والنباتات الطبية والمناظر الطبيعية والحياة البرية بالتساوي نسبيًا ؛ ومع ذلك، تمت دراسة المعرفة المتعلقة بالمناخ في كثير من الأحيان بشكل أقل. من بين 63 ورقة ذكرت صراحة انتقال المعرفة ...